2021
DOI: 10.1293/tox.2020-0058
|View full text |Cite
|
Sign up to set email alerts
|

Swim bladder tumors in the wavy medaka (<i>Oryzias latipes</i>)

Abstract: Swim bladder tumors were detected in three out of 28 wavy medakas aged about 2 years old, all of which displayed abnormal swimming patterns caused by their spinal curvature. The tumors were located in the dorsal abdominal cavity. The swim bladder lumen was not detected in the region where it was originally assumed to be located, and that region was replaced with adipose tissue. The tumors were non-invasive, expansile, and encapsulated solid masses composed of a homogenous population of well-differentiated, den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 23 publications
(28 reference statements)
1
7
0
Order By: Relevance
“…The morphology of swim bladder tumor in the present case was similar to that in the wavy medakas, described in our previous report 11 ; however, the rete mirabile was enlarged by the hyperplastic capillary plexus in this case. The proliferated rete mirabile in the swim bladder tumors was also detected in Sparus aurata 13 .…”
supporting
confidence: 88%
See 3 more Smart Citations
“…The morphology of swim bladder tumor in the present case was similar to that in the wavy medakas, described in our previous report 11 ; however, the rete mirabile was enlarged by the hyperplastic capillary plexus in this case. The proliferated rete mirabile in the swim bladder tumors was also detected in Sparus aurata 13 .…”
supporting
confidence: 88%
“…. In contrast, the incidence of swim bladder tumors is markedly higher at 10.7% (3/28) in wavy medakas11 . Additionally, it is reported that the juvenile fishes with skeletal deformations exhibit a high prevalence of spontaneous proliferative changes in the swim bladder, including the swim bladder tumors.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…In Case I, the medaka showed dorso-ventral curvature of its vertebral column, the so-called wavy medaka. In previous reports, the occurrence of a spontaneous swim bladder tumor in fish is considered to be closely associated with various types of skeletal deformation, and wavy medaka in particular 20,21 .…”
mentioning
confidence: 99%